Cultura e agroecologia: a influência de aspectos culturais na adoção e manutenção da agricultura agroecológica - Oliveira, Evandro de (2014)
In contemporary society the conventional agricultural model permeated with the use of pesticides and chemical fertilizers has gotten more importance since the late 1950 and it has spread throughout the world. This conventional agriculture benefited the large landowner, leaving the small producer on the fringes of rural development. Facing this unfavorable panorama to family farming, many small-scale farmers have opted for rural exodus, while those who stayed in rural areas try to survive by choosing alternative production. One of the alternatives to the family-owned is the Agroecology, which aims to produce food in a sustainable manner as well as the development of small farmers. However, in the Agroecology there are many obstacles that make it difficult the diffusion and maintenance of this agriculture. One of the issues that influence the adoption and perpetuation of Agroecology is about cultural elements. The existing culture in rural areas is a hybrid culture, whatever, it. is not a "pure" rural culture, but a culture in which is included several features that are unique to the rural environment. In this respect, many cultural aspects of rural surroundings influence the ecological agriculture. But it's not just rural cultural factors that influence Agroecology, cultural issues "external" the countryside also influence this agricultural practice. It is worth mentioning that culture also provides factors that contribute directly or indirectly in Agroecology, and also some cultural aspects "internal" or "external" in the rural environment that can intervene in Agroecology. It is in this perspective that the main objective of the dissertation is, to identify and understand the influence of culture on the adoption and maintenance of Agroecology. The study will be done with Agroecological family farmers associated in the Association of Family Farmers and Ecological Medianeira-AAFEMED. This association is located in Medianeira, Parana. The theoretical basis of the dissertation is based on theoretical-methodological ideas of Karl Mannheim, Norman Long, Michel Callon and Bruno Latur and some authors who work with the themes, culture, agroecology and family farming. The research will attempt to expose the cultural networks that influence the adoption and maintenance of Agroecology